Reading civil war by Guns N'Roses : a semiotics of poetry analysis a graduating paper - Adam Nursyifa Fikri Firmansyah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/adil,c.1